História de vida de laetacara aff. araguaiae ottoni & costa, 2009 (Perciformes, Cichlidae) em dois riachos no noroeste do Estado de São Paulo, Brasil - de Filho, Paulo Sérgio Souza [UNESP]; Casatti, Lilian [UNESP] (My University, 2010)
The structure in size, density, feeding, fecundity, and presence of ectoparasites in two populations of Laetacara aff. araguaiae was investigated in two streams, in Northwestern São Paulo State, one structurally more heterogeneous (HET) and other relatively more simplified (SIM). Six samples were taken in each stream, three in the wet period (October, December/2007, February/2008) and three in the dry period (April, July, September/2008), which were performed during 15 minutes of sampling in each stream, using a 3 mm-mesh sieve. A total of 118 individuals in HET stream (49 in the wet season and 69 in dry) and 146 in SIM stream were captured (82 in wet and 64 in dry). Fish collected in HET stream were larger than those collected in the SIM, both in wet and dry periods. The density was similar between two streams, with an increase agreeing with the peak of the dry period. Fragments of aquatic insects were the most important items of diet, which showed little spatial and temporal variation. Fecundity was significantly higher in HET, ranging from 977 to 1,602 oocytes, in contrast with females of the SIM, which had 338 to 814 oocytes. The ectoparasites (Digenea) were present only in specimens of the SIM, and were attached to the fins (dorsal and anal) with higher prevalence in October. Feeding and density were similar in the two populations of Laetacara aff. araguaiae, contrasting with the structure in size and fecundity. The differences in these demographic parameters do not occur randomly and are possibly reflecting the high rates of parasitism in the more simplified stretch that determines lower resources allocation to growth and reproduction of fishes in this population.
Life history of Laetacara aff. araguaiae Ottoni & Costa, 2009 (Perciformes, Cichlidae) in two streams in Northwestern São Paulo State, Brazil
Keywords: Density; Ectoparasites; Fecundity; Feeding; Heterogeneity; Structure in size; Upper paraná